Controllable nonreciprocal spin Seebeck effect in helimagnets - Xiao-Feng Chen; Pei-Jia Hu; Ai-Min Guo; Tie-Feng Fang; Chenglong Jia (New Journal of Physics)
Nonreciprocal transport plays a crucial role in various fundamental challenges and applications in the fields of physics and technology. Here, we investigate the thermal spin transport property of helimagnets using the Non-equilibrium Green’s Function method. Our results reveal that the spin currents driven by a temperature difference remain reciprocal in the absence of an external magnetic field and magnetic anisotropy. However, a nonreciprocal spin Seebeck effect arises when an external magnetic field or magnetic anisotropy is introduced in the system. Notably, the nonreciprocal effect can be amplified with increasing strength of the magnetic field or magnetic anisotropy. Furthermore, we demonstrate that this effect persists even in the presence of Gilbert damping. A detailed analysis highlights how the breaking of mirror symmetry contributes to asymmetries in magnon spin transmission, ultimately leading to nonreciprocal behavior.